Solar photovoltaic (PV) maximum power point tracker (MPPT) using variable step size perturb and observe (P&O) algorithm - Ibrahim Mohammed, Omer Jamal Eldin (2014)
Photovoltaic PV solar known for the low energy convergence efficiency when compared to other types of energy sources. Since PV Solar have nonlinear characteristic, it gives its maximum output at the Maximum Power Point MPP. This point affected by sun irradiation, temperature and the degree of the sun irradiance. It economically essential to utilize the maximum output of PV solar. Hence, a proper Maximum Power Point Tracking (MPPT) can achieve this task under fast weather variation. In this project, modified Perturb and Observe (P&O) or more commonly known as variable step size P&O method was introduced and implemented throughout the project to overcome the common drawbacks of conventional P&O method as solar irradiation changes. The operation of the entire solar MPPT system was observed through theoretical approaches using MATLAB/Simulink simulation. The system was further explored with the inclusion of surrounding temperature. Double diode modeling circuit will be used for higher accuracy and efficiency.